MEMBANGUN DEEP RELATIONSHIPS ANTARA MANUSIA DENGAN ALLAH DALAM NARASI AIR BAH KEJ 7:1-24 - Eric Yohanis Tatap; Sirus Yulius Mbusa (Aggiornamento, 2020)
Corona Virus Disease 2019 or Covid-19 is a hot topic for human research today. The virus that is currently sweeping to create great fear and problems for mankind. Departing from that fact, this article wants to review fears and problems that occur in human life. The problem is in the form of broken relationships between human’s fellowship and even towards God. This issue is elaborated with The Flood narrative found in Genesis 7:1-24. In this paper, the methodology is used qualitative with reflective nuances. The finding is that mankind is being hated by God, so human needs self-awareness to continue to have a deep relationship with God. The relevance of this paper is to build human awareness who are often tenuous in their relationship with God of the Universe.